CARBON SEQUESTRATION POTENTIAL IN MANGROVE FORESTS IN HAI PHONG COASTAL AREAS - Hung, Vu Manh; Tien, Dam Duc; Luong, Cao Van (Vietnam Journal of Marine Science and Technology, 2015)
Mangrove is known as a big carbon sink in coastal areas. It is an important organic carbon source which provides for coastal ecosystems. The assessment of the carbon sequestration potential of mangrove contributes to making a scientific base for mangrove conservation and rehabilitation. In this study, the carbon sequestration of mangrove in the Hai Phong coastal areas was measured at three dominant species of mangrove Rhizophora stylosa Griff; Kandelia obovata Sheue, Liu & Yong and Sonneratia caseolaris (L.) Engl. The result of the assessment was described by the net canopy photosynthesis (PN), above and below ground biomass (AGB and BGB), and organic carbon content in sediment. The result showed that the PN ranged from 31.94 ± 1.59 tC.ha-1.yr-1 to 34.83 ± 1.95 tC.ha-1.yr-1 with the R. stylosa community being highest. Above and below ground biomass C stock ranged from 4.03 ± 0.31 t.ha-1 to 294.43 ± 24.67 t.ha-1 and from 2.38 ± 0.16 t.ha-1 to 114.16 ± 8.9 t.ha-1, respectively. S. caseolaris community had the highest biomass and R. stylosa community had the lowest biomass. The measurements of C stock in mangrove biomass for three species were R. stylosa (2.69 ± 0.19 t.ha-1); K. obovata (6.72 ± 0.34 t.ha-1) and S. caseolaris (171.61 ± 14.1 t.ha-1). The organic carbon content of sedimentscores at 10 cm depth ranged from 685.63 milligram.kg-1 of se. dry to 2676.64 milligram.kg-1 of se. dry and at 40 cm depth ranged from 937.38 milligram.kg-1 of se. dry to 2557.55 milligram.kg-1 of se. dry. The total organic carbon was stored highest in the R. stylosa community.